2011 Third International Conference on Measuring Technology and Mechatronics Automation 2011
DOI: 10.1109/icmtma.2011.90
|View full text |Cite
|
Sign up to set email alerts
|

Affect of Different Preprocessing Methods on Principal Component Analysis for Soil Classification

Abstract: Fast classification of soil with different texture is essential for site-specific application of different inputs into farmland. Total 203 soil samples with five textures were collected from Silsoe Experimental Farm, Cranfield University, England. Using a Vis/NIR spectrophotometer (Tech5, Germany), spectra of soil samples were recorded for the study. Amongst the pre-processing methods, smoothing with moving average(MA), multiplicative scatter correction(MSC), standard normal variation(SNV), de-trending(DT), ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…As a consequence of exceeding field capacity, there will be infiltration and nutrient loss eventually. Then soil type must be identified and based on each kind, the proposed system can adjust the amount of water required [10] [11].…”
Section: Design Of Fuzzy Logic Controllermentioning
confidence: 99%
“…As a consequence of exceeding field capacity, there will be infiltration and nutrient loss eventually. Then soil type must be identified and based on each kind, the proposed system can adjust the amount of water required [10] [11].…”
Section: Design Of Fuzzy Logic Controllermentioning
confidence: 99%
“…SIMCA models were developed using different data pretreatments that included smoothing, multiplicative scatter correction (MSC), standard normal variate (SNV), baseline correction (BC), normalise and first and second derivatives. 24,37 The first and second derivative and smoothing transforms are based on a Savitzky-Golay 38 polynomial filter. The number of significant PCs in the model of each class was evaluated using leave-one-out cross-validation.…”
Section: Chemometrics Of Spectral Datamentioning
confidence: 99%
“…These SIMCA models correctly classified 100% of the samples in the test set included as "unknown" samples ( Table 2). Yang et al 24 also reported that first derivatives of NIR spectra produce the best results for the PCA classification of soil texture as compared to MSC, SNV, BC and second-derivative pre-processing methods.…”
Section: Simca Classification Of Soil Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil spectral signature is the radiation reflected as a function of the wavelength [9]. Recent researchers have indicated that visible and near-infrared, diffuse reflectance spectroscopy (VINR-DRS) and specific band from hyperspectral sensor data [10,[11][12][13][14][15]. Near-Infrared spectroscopy can be used to analyze heavy metal contents in soil such as zinc (Zn), copper (Cu), lead (Pb), chrome (Cr), and nickel (Ni) [16].…”
Section: Introductionmentioning
confidence: 99%